Post-glacial Hirnantian (upper Ordovician) bryozoans from western Argentina: implications for survival and extinction patterns - Halpern, Karen (2014)
Two bryozoan taxa occurring in the Hirnatian (Upper Ordovician) deposits in western Argentina document a first postglacial community associated with a mid-to high-latitude brachiopod assemblage, known as the typical Hirnantia fauna, in the Argentine Precordillera. Helopora fragilis Hall and an indeterminate phyloporinid occur within a thin but conspicuous shell bed that overlies diamictitic deposits from the lower member of the Don Braulio Formation. The abundance of well preserved specimens of bryozoans together with the dominance of suspension feeders suggests a mid-shelf setting (offshore transition) with an intermediate to low sedimentation rate, low turbidity, and nutrient-rich conditions. Hirnantian bryozoan assemblages identified from tropical and subtropical regions are rather rare, and this assemblage represents the first high-latitude Hirnantian record. The low diversity of bryozoans may be related to high-latitude location of Argentina during the Late Ordovician. Helopora occurs mainly in Laurentia with several species occurring in the Katian and with a few Hirnatian occurrences in Gondwana. This broad distribution may imply that this genus had a broad environmental tolerance. It is one of the genera that successfully crossed the Ordovician/Silurian boundary. However, although this genus shows a post-extinction diversification and a more widespread distribution in Laurentia (with numerous species recorded in the Silurian and Devonian of Canada, Russia and China), it became extinct in Gondwana. We hypothesize that environmental conditions after the Ordovician/Silurian boundary may have prevented the settlement of bryozoans and caused the extinction of Helopora in the Argentine Precordillera.